Pengaruh Keterampilan Guru Mengadakan Variasi dalam Mengelola Kelas - Amala Sundari; Fany Isti Fauzia; Rifqi Taufiqul Hakim; Tia Lahera (Journal on Education, 2023)
In creating a creative learning process, teachers must have skills and develop them. One of the To produce creative learning activities, teachers must have skills and develop them. One of the eight basic teaching skills is variety. The purpose of this study was to determine the influence of the teacher's skills in teaching variations in managing the class. In this study the authors used the method of library research (library research), in this research in the literature study by reading books and data sources that contain data from various literature in the form of relevant journals, articles, books. The results of the study showed that there were several significant influences regarding the teacher's skills to hold variations in managing the class including increasing student learning interest, increasing student learning outcomes, increasing student learning achievement, increasing student learning activeness, increasing student learning motivation. Therefore, the teacher should pay attention to the skills of holding variations in managing the class.